Cellulose conversion under heterogeneous catalysis - Dhepe, Paresh Laxmikant; Fukuoka, Atsushi (ChemSusChem, 2008)
In view of current problems such as global warming, high oil prices, food crisis, stricter environmental laws, and other geopolitical scenarios surrounding the use of fossil feedstocks and edible resources, the efficient conversion of cellulose, a non-food biomass, into energy, fuels, and chemicals has received much attention. The application of heterogeneous catalysis could allow researchers to develop environmentally benign processes that lead to selective formation of value-added products from cellulose under relatively mild conditions. This Minireview gives insight into the importance of biomass utilization, the current status of cellulose conversion, and further transformation of the primary products obtained
Keywords: Biomass; cellulose; heterogeneous catalysis; supported catalysts

Sustainable green catalysis by supported metal nanoparticles - Fukuoka, Atsushi; Dhepe, Paresh Laxmikant (Chemical Record, 2009)
The recent progress of sustainable green catalysis by supported metal nanoparticles is described. The template synthesis of metal nanoparticles in ordered porous materials is studied for the rational design of heterogeneous catalysts capable of high activity and selectivity. The application of these materials in green catalytic processes results in a unique activity and selectivity arising from the concerted effect of metal nanoparticles and supports. The high catalytic performances of Pt nanoparticles in mesoporous silica is reported Supported metal catalysts have also been applied to biomass conversion by heterogeneous catalysis Additionally, the degradation of cellulose by supported metal catalysts, in which bifunctional catalysis of acid and metal plays the key role for the hydrolysis and reduction of cellulose, is also reported. (C) 2009 The Japan Chemical Journal Forum and Wiley Periodicals, Inc. Chem Rec 9: 224-235: 2009: Published online in Wiley InterScience (www.intersciencewiley.corn) DOI 10.1002/tcr.200900004
Keywords: Biomass; cellulose; CO oxidation; Mesoporous silica; supported metal catalyst

Solid-acid-based process for the conversion of hemicellulose - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (Green Chemistry, 2010)
We describe a solid-acid-catalyzed conversion of hemicellulose (a component of lignocellulosic material) into xylose, arabinose and furfural in aqueous media.

One pot and single step hydrolytic process for the conversion of lignocellulose into value added chemicals - Dhepe, Paresh Laxmikant; Sahu, Ramakanta (WO2011092711 A1, 2011)
The present invention provides a single step hydrolytic process for the conversion of lignocellulose, into value added chemicals wherein said process is catalyzed by at least one heterogeneous solid acid catalyst selected from a group comprising of zeolites, zeolites with Si/metal, mesoporous silica, oxides and phosphates, clays, ion-exchange resins, heteropolyacids, various sulfates, phosphates, selenates, crystalline materials and amorphous materials.

Ce-Ni mixed oxide as efficient catalyst for H-2 production and nanofibrous carbon material from ethanol in the presence of water - Fang, Wenhao; Pirez, Cyril; Capron, Mickael; Paul, Sebastien; Raja, Thirumalaiswamy; Dhepe, Paresh Laxmikant; Dumeignil, Franck; Jalowiecki-Duhamel, Louise (RSC Advances, 2012)
Hydrogen production from ethanol steam reforming (H2O/C2H5OH = 3) was studied over Ce-Ni based catalysts issued from different preparation methods (co-precipitation (CP), impregnation (IMP) and incipient wetness impregnation (IWI)). Catalysts prepared by the CP method exhibit higher activity and much better stability compared to the other two types of catalysts. The Ni1CeOY-CP catalyst is able to completely convert ethanol at 450 degrees C to H-2, CO2 and CH4 (almost no CO is observed), with a H-2 yield of 3 moles of hydrogen produced per mole of ethanol converted. A very high H-2 yield of 4.6 mol mol(EtOH)(-1) is achieved over the Ni1CeOY-CP mixed oxide at 650 degrees C. Correlations between the preparation method, catalytic activity and stability, and type of carbon deposition are discussed. The CP method forms very active small sized NiO (15 nm) and CeO2 (4 nm) nanoparticles, leading to the formation of a lower amount of carbon deposition in the form of nanofibrous carbon materials, the size of which depends on the Ni related nanoparticles. For CP catalysts, the graphitic filaments obtained correspond to carbon nanofibers (CNFs) and carbon nanotubes (CNTs) with a much smaller and homogenous size compared to the filamentous carbon formed over the catalysts issued from the other preparation methods, in relation to the active particles size. The catalytic stability is attributed to the type of carbon formed.

One-Pot method for the selective conversion of hemicellulose from crop waste into C5 sugars and furfural by using solid acid catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Chemsuschem, 2012)
We present a solid-acid catalyzed one-pot method for the selective conversion of solid hemicellulose without its separation from other lignocellulosic components, such as cellulose and lignin. The reactions were carried out in aqueous and biphasic media to yield xylose, arabinose, and furfural. To overcome the drawbacks posed by mineral acid methods in converting hemicelllulose, we used heterogeneous catalysts that work at neutral pH. In a batch reactor, these heterogeneous catalysts, such as solid acids (zeolites, clays, metal oxides etc.), resulted in >90% conversion of hemicellulose. It has been shown that the selectivity for the products can be tuned by changing the reaction conditions, for example, a reaction carried out in water at 170 degrees C for 1 h with HBeta (Si/Al=19) and HUSY (Si/Al=15) catalysts gave yields of 62 and 56% for xylose and arabinose, respectively. With increased reaction time (6 h) and in presence of only water, HUSY resulted in yields of 30% xylose+arabinose and 18% furfural. However, in a biphasic reaction system (water+p-xylene, 170 degrees C, 6 h) yields of 56% furfural with 17% xylose+arabinose could be achieved. It was shown that with the addition of organic solvent the furfural yield could be increased from 18 to 56%. Under optimized reaction conditions, >90% carbon balance was observed. The study revealed that catalysts were recyclable with a 20% drop in activity for each subsequent run. It was observed that temperature, pressure, reaction time, substrate to catalyst ratio, solvent, and so forth had an effect on product formation. The catalysts were characterized by means of X-ray diffraction, temperature-programmed desorption of NH3, inductively coupled plasma spectroscopy, elemental analysis, and solid-state NMR (Si-29, Al-27) spectroscopy techniques.
Keywords: analytical methods; Biomass; carbohydrates; heterogeneous catalysis; zeolites

Efficient, stable, and reusable silicoaluminophosphate for the one-pot production of furfural from hemicellulose - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ACS Catalysis, 2013)
Development of stable, reusable, and water tolerant solid acid catalysts in the conversion of polysaccharides to give value-added chemicals is vital because catalysts are prone to undergo morphological changes during the reactions With the anticipation that silicoaluminophosphate (SAPO) catalysts will have higher hydrothermal stability, those were synthesized, characterized, and employed in a one-pot conversion of hemicellulose. SAPO-44 catalyst at 170 degrees C within 8 h could give 63% furfural yield with 88% mass balance and showed similar activity up to at least 8 catalytic cycles. The morphological studies revealed that SAPO catalysts having hydrophilic characteristics are stable under reaction conditions.
Keywords: furfural; Hemicellulose; hydrophilicity; SAPO; water-tolerant catalyst; zeolite

Influence of properties of SAPO's on the one-pot conversion of mono-, di- and poly-saccharides into 5-hydroxymethylfurfural - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (RSC Advances, 2013)
Synthesis of 5-hydroxymethylfurfural (5-HMF) from biomass derived mono-and poly-saccharides is gaining importance because of its usefulness in the preparation of important chemicals. In our work, we have synthesized several silicoaluminophosphate (SAPO) catalysts, and have shown that in the absence of any other pH modifying reagents, those are active in converting mono-and poly-saccharides into 5-HMF under biphasic reaction condition at 175 degrees C. Particularly, SAPO-44 catalyst showed the best activity in the conversion of fructose to yield 78% 5-HMF with 88% selectivity. On the contrary, all other catalysts showed lower yields (H-MOR: 63%, SAPO-5: 32%, 2DCT: 60%). Over SAPO-44, good yields for 5-HMF were observed when glucose (67%), maltose (57%), cellobiose (56%) and starch (68%) were used as substrates. Recycle study carried out with SAPO-44 catalyst in the fructose conversion reaction showed marginal decrease in the activity up to 3rd run and then afterwards constant activity was observed up to 5th run (1st: 78%, 2nd: 71%, 3rd: 66%, 4th: 65%, 5th: 65%). Catalyst characterizations revealed that SAPO catalysts have higher hydrophilic nature than H-MOR (Si/Al = 10) and hence it is postulated that this property may help in achieving better results. Further studies on the catalyst characterizations revealed that SAPO-44 undergoes modifications in its structure. However, ICP-OES data suggests that Al and/or P are not leached out in the solution indicating that change in local environment around elements is possible. The influence of acid amount, type of acid site etc. on the catalytic activity is discussed and found out that strong acid sites are required to boost the 5-HMF yields.

Acidic ionic liquids catalyzed depolymerization of lignin - Dhepe, Paresh Laxmikant; Kelkar, Ashutosh Anant; Matsagar, Babasaheb Mansub; Singh, Sandip Kumar (WO2014181360 A1, 2014)
The present invention discloses a process for depolymerization of lignin to yield substituted phenolic monomers using Brönsted ionic liquid as catalyst under mild reaction conditions to obtain an overall yield of monomers up to 97%.

Conversion of hemicellulose using acidic ionic liquids - Dhepe, Paresh Laxmikant; Matsagar, Babasaheb Mansub (WO2015111086 A1, 2014)
The present invention discloses one pot process for the conversion of hemicellulose into C5 sugars using ionic liquids in water media.

Exceptionally high yields of furfural from assorted raw biomass over solid acids - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Development of stable and recyclable solid acid catalysts in the efficient valorisation of hemicellulose to yield C-5 sugars and furfural is vital to boost the prospects of using lignocelluloses for chemicals synthesis. Using an silicoaluminophosphate, namely SAPO-44, as a catalyst, an environmentally benign process of furfural synthesis from diversified real substrates (without any treatment or the need for separation of its components) is shown. In an efficient one-pot methodology, at 443 K and in the presence of a biphasic solvent system, selective conversions of hemicelluloses from raw biomass (bagasse, rice husk and wheat straw) to extraordinarily high yields of furfural of about 93% were attainable. Under similar reaction conditions, an 82% yield of furfural is also achievable directly from isolated hemicellulose within 10 h. Hydrophilic SAPO-44, having higher hydrothermal stability, showed similar activity for all the substrates for a minimum of up to 8 times in recycling runs. Various physicochemical characterizations (X-ray diffraction, thermogravimetric analysis-derivative thermogravimetry, temperature programmed desorption-NH3, N-2 sorption, solid-state nuclear magnetic resonance spectroscopy) of fresh and spent catalysts were used to improve SAPO-44 stability.

Silica and zirconia supported tungsten, molybdenum and gallium oxide catalysts for the synthesis of furfural - Bhaumik, Prasenjit; Kane, Tanushree; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2014)
SiO2 and ZrO2 supported W, Mo and Ga oxide catalysts were prepared by a sol-gel and wet-impregnation method. The 10 wt% WO3/SiO2 (sol-gel) catalyst showed 61 +/- 2% furfural yield from hemicellulose in a one-pot fashion for at least 8 cycles. Based on XRD, TPD and Hammett acidity characterizations, the catalyst structure-activity correlation was drawn.

Solid acid catalyzed depolymerization of lignin into value added aromatic monomers - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Depolymerization of lignin to produce value-added aromatic monomers has attracted a lot of attention since these monomers can potentially be used as fuel additives (octane enhancers) and in turn can improve the prospects of cellulosic ethanol technology to become economically feasible. Here we show that solid acid catalysts could efficiently convert lignin into value added aromatic monomers with 60% yields and ca. 95% mass balance when depolymerization reactions were carried out at 250 degrees C for 30-120 minutes. We found that the reaction parameters have a remarkable effect on improving the yields.

Solid base supported metal catalysts for the oxidation and hydrogenation of sugars - Tathod, Anup; Kane, Tanushree; Sanil, E. S.; Dhepe, Paresh Laxmikant (Journal of Molecular Catalysis A-Chemical, 2014)
Pt impregnated on gamma-Al2O3 (acidic support) and hydrotalcite (basic support) catalysts were synthesized, characterized and used in the oxidation and hydrogenation reactions of C5 and C6 sugars. In the absence of homogeneous base, 83% yield for gluconic acid; an oxidation product of glucose can be achieved over Pt/hydrotalcite (HT) catalyst at 50 degrees C under atmospheric oxygen pressure. Similarly, 57% yield for xylonic acid, an oxidation product of xylose is also possible over Pt/HT catalyst. Hydrogenation of glucose conducted using Pt/gamma-Al2O3 + HT catalytic system showed 68% sugar alcohols (sorbitol + mannitol) formation. The 82% yield for C5 sugar alcohols (xylitol + arabitol) was obtained by subjecting xylose to hydrogenation over Pt/gamma-Al2O3 + HT at 60 degrees C. UV analysis helped to establish the fact that under alkaline conditions sugars prefer to remain in open chain form in the solution and thus exposes -CHO group which further undergoes oxidation and hydrogenation reactions to yield acids and alcohols. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Oxidation; Solid base; Sugars; Supported metal catalysts

Synthesis of 2,5-furandicarboxylic acid by the aerobic oxidation of 5-hydroxymethyl furfural over supported metal catalysts - Sahu, Ramakanta; Dhepe, Paresh Laxmikant (Reaction Kinetics Mechanisms and Catalysis, 2014)
Supported Pt catalysts are synthesized, characterized and are used in the liquid phase air oxidation of 5-hydroxymethylfurfural (HMF) to 2,5-furandicarboxylic acid (FDCA). Under the optimum reaction conditions of a stepwise increase in the reaction temperature (75 and 140 degrees C for 12 h each), we achieved as high as 96 % FDCA yield in presence of 1 bar oxygen pressure over Pt/c-Al2O3. It is shown that as the oxygen pressure increases (1-10 bar), the FDCA yields decrease, since at higher partial pressure of oxygen, overoxidation reactions of substrate and product(s) are possible. It is interesting to note that even with air as an oxidant, we obtained similar yields of FDCA as that with oxygen. Moreover, the effects of base (weak or strong), its concentration (equimolar or excess) were studied in detail. It is important to increase the reaction temperature in a stepwise manner to achieve higher yields of FDCA since at higher temperatures HMF undergoes self-degradation and thus the yields of FDCA decrease. The self-degradation of HMF is also proved by undertaking the reaction under nitrogen environment. The study on the effect of substrate-to-catalyst ratio is done to improve up on the economics of overall process. The effect of supports (reducible and non-reducible) and their oxygen storage capacity is discussed and is proposed to be one of the factors to change the course of reaction. Furthermore, we have shown that FDCA formed in the reaction can be successfully isolated (91 %, isolated yield) in the pure form and its purity is confirmed by NMR, melting point, and elemental analysis. The catalysts were characterized with X-ray powder diffraction, transmission electron microscopy and inductively coupled plasma-optical emission spectroscopy techniques.
Keywords: Biomass; FDCA; green chemistry; heterogeneous catalyst; HMF; Impregnation; Oxidation

Towards efficient synthesis of sugar alcohols from mono- and poly-saccharides: role of metals, supports & promoters - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Green Chemistry, 2014)
{Biomass derived sugar alcohols (xylitol, arabitol) find numerous uses in the food, oral hygiene and pharmaceutical industries. Their direct synthesis from poly-saccharides, however, still remains an immense challenge. In this study, we demonstrate in detail the effects of metals, supports and promoters in enhancing the yields of sugar alcohols from mono- and poly-saccharides. We undertook synthesis of bimetallic catalysts, M-M'/S (M

Value addition to lignocellulosics and biomass-derived sugars: an insight into solid acid-based catalytic methods - Bhaumik, Prasenjit; Deepa, Ayillath K.; Kane, Tanushree; Dhepe, Paresh Laxmikant (Journal of Chemical Sciences, 2014)
For the synthesis of important platform chemicals such as sugars (xylose and arabinose) and furans (furfural and 5-hydroxymethylfurfural (HMF)) from carbohydrates (hemicellulose and fructose) solid acid catalysts are employed. Similarly, over solid acid catalysts, conversion of lignin into aromatic monomers is performed. It is observed that in the dehydration of fructose, because of higher hydrothermal stability, silicoaluminophosphate (SAPO) catalysts give better activity (78% HMF yield) compared with other solid acid catalysts (<63% HMF yield) at 175 degrees C. Particularly, SAPO-44 catalyst can be reused at least 5 times with marginal decrease in the activity. Zeolite, BUSY (Si/Al = 15) is active in the conversion of isolated (pure) hemicellulose to produce 41% C-5 sugars in water. The catalyst is also active in the selective conversion of hemicellulose from bagasse to yield 59% C-5 sugars. It is possible to obtain high yields of furfural (54%) directly from bagasse if instead of water, Water+toluene solvent system is used. Depolymerization of lignin using HUSY catalyst produced aromatic monomers with 60% yield at 250 degrees C. A detailed catalyst characterization study is performed to understand the correlation between catalyst activity and morphology. To understand the effect of impurities present in the substrate over solid acid catalysts, metal-exchange study is carried out.
Keywords: aromatic monomers; Biomass; furans; Hemicellulose; lignin; solid acid catalyst

Bronsted acidic ionic liquid-catalyzed conversion of hemicellulose into sugars - Matsagar, Babasaheb M.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Development of a competent method for the conversion of hemicellulose, a lignocellulosic component, into sugars is essential. In a one-pot method, Bronsted acidic ionic liquid (BAIL)-catalyzed hydrolysis of hardwood hemicellulose at 160 degrees C in water media gave C5 sugars (xylose + arabinose) in 87% yield. The efficiency of the ILs and their acid strength both followed the similar trend, [C3SO3HMIM][HSO4] > [C3SO3HMIM][PTS] > [C3SO3HMIM][Cl] > [BMIM][Cl]. The ion-dipole-type interaction present between the BAIL and the substrate, which is proposed by the H-1 NMR study, is suggested to help in achieving better activity with BAIL than with mineral acid, H2SO4.

Conversion of biomass into sugars - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant; Dmitry, Murzin; Olga, Simakova (Biomass sugars for non-fuel applications, 2015)

Conversion of concentrated sugar solutions into 5-hydroxymethyl furfural and furfural using Bronsted acidic ionic liquids - Matsagar, Babasaheb M.; Munshi, Mudassir K.; Kelkar, Ashutosh A.; Dhepe, Paresh Laxmikant (Catalysis Science & Technology, 2015)
Catalytic amounts of recyclable Bronsted acidic ionic liquids (BAILs) yielded HMF (73%) and furfural (81%) with high selectivity from highly concentrated solutions of D-fructose (40 wt%) and D-xylose (3 wt%), respectively. With a 6 wt% D-xylose solution, 73% yield was observed. An activity-property correlation of BAIL is established.

Effects of careful designing of SAPO-44 catalysts on the efficient synthesis of furfural - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Today, 2015)
Considering the growing importance of furfural, it is necessary to develop a robust solid acid catalyst for the conversion of xylan (hemicelluloses) into furfural in a one-pot method. In this study, the effects of various components (Si, Al and P) and crystallization time on the preparation of acidic materials and their properties are extensively described. It is seen that with the increase in crystallization time (0, 48, 96, 176 h) during the synthesis of silicoaluminophosphate (SAPO-44), materials morphology changes from amorphous to AFI to CHA and the best activity for furfural synthesis (82%) from xylan was observed with SAPO-44 catalyst aged for 176 h. Since, acidity in the SAPO-44 is guided by the incorporation of Si in the ALPO framework, study on Si molar concentration (0.8, 1.0, 1.2, 1.4 and 1.6) in SAPO-44 was carried out and it was observed that SAPO-44 having 1.0 mole of Si content is the best catalyst for the xylan/xylose conversion to furfural. Catalyst structure-activity correlation is thoroughly defined with the help of several physico-chemical properties. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Biomass; furfural; Hemicellulose; SAPO-44; Xylose

Efficient method for the conversion of agricultural waste into sugar alcohols over supported bimetallic catalysts - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2015)
Promoter effect of Sn in the PtSn/gamma-Al2O3 (AL) and PtSn/C bimetallic catalysts is studied for the conversion of variety of substrates such as, C5 sugars (xylose, arabinose), C6 sugars (glucose, fructose, galactose), hemicelluloses (xylan, arabinogalactan), inulin and agricultural wastes (bagasse, rice husk, wheat straw) into sugar alcohols (sorbitol, mannitol, xylitol, arabitol, galactitol). In all the reactions, PtSn/AL showed enhanced yields of sugar alcohols by 1.5-3 times than Pt/AL. Compared to C, AL supported bimetallic catalysts showed prominent enhancement in the yields of sugar alcohols. Bimetallic catalysts characterized by X-ray diffraction study revealed the stability of catalyst and absence of alloy formation thereby indicating that Pt and Sn are present as individual particles in PtSn/AL. The TEM analysis also confirmed stability of the catalysts and XPS study disclosed formation of electron deficient Sn species which helps in polarizing carbonyl bond to achieve enhanced hydrogenation activity. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Agricultural waste; Bimetallic catalyst; Hydrogenation; Monosaccharides; Polysaccharides

Lignin depolymerization into aromatic monomers over solid acid catalysts - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (ACS Catalysis, 2015)
It is imperative to develop an efficient and environmentally benign pathway to valorize profusely available lignin, a component of nonedible lignocellulosic materials, into value-added aromatic monomers, which can be used as fuel additives and platform chemicals. To convert lignin, earlier studies used mineral bases (NaOH, CsOH) or supported metal catalysts (Pt, Ru, Pd, Ni on C, SiO2, Al2O3, etc.) under a hydrogen atmosphere, but these methods face several drawbacks such as corrosion, difficulty in catalyst recovery, sintering of metals, loss of activity, etc. Here we show that under an inert atmosphere various solid acid catalysts can efficiently convert six different types of lignins into value-added aromatic monomers. In particular, the SiO2Al2O3 catalyst gave exceptionally high yields of ca. 60% for organic solvent soluble extracted products with 95 +/- 10% mass balance in the depolymerization of dealkaline lignin, bagasse lignin, and ORG and EORG lignins at 250 degrees C within 30 min. GC, GC-MS, HPLC, LC-MS, and GPC analysis of organic solvent soluble extracted products confirmed the formation of aromatic monomers with ca. 90% selectivity. In the products, confirmation of retention of aromatic nature as present in lignin and the appearance of several functional groups has been carried out by FT-IR and H-1 and C-13 NMR studies. Further, isolation of major products by column chromatography was carried out to obtain aromatic monomers in pure form and their characterization by NMR is presented. A detailed characterization of six different types of lignins obtained from various sources helped in substantiating the catalytic results obtained in these reactions. A meticulous study on fresh and spent catalysts revealed that the amorphous catalysts are preferred to obtain reproducible catalytic results.
Keywords: aromatic monomers; Biomass; column chromatography; depolymerization; lignin; solid acid catalysts

Ionic liquids catalyzed lignin liquefaction: mechanistic studies using TPO-MS, FT-IR, RAMAN and 1D, 2D-HSQC/NOSEY NMR - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Green Chemistry, 2016)
Valorization of a profusely available alternate resource, biomass and in particular its 3-D intricate component lignin into low molecular weight aromatic products are used as platform chemicals and fuel additives, and developing a low temperature catalytic process is imperative in preserving atom efficiency. Ionic liquids, due to their unique properties, offer an advantage to develop such methods under milder conditions. Herein, we show use of -SO3H functionalized imidazolium based various recyclable Bronsted acidic ionic liquids (BAILs) in catalytic quantity under ambient pressure at 120 degrees C for depolymerization of lignin (60 000 g mol(-1)) into THF soluble products with high efficiency (78% yield, 95% +/- 5% mass balance). The decoding of this efficiency by 1D and 2D (HSQC/NOSEY) NMR, FT-IR and RAMAN studies exemplify that the -OH group(s) interact with the electron deficient BAIL cation. The mechanistic insights unraveled in this study open a plethora of opportunities to design catalysts for developing efficient processes.

Isolation of lignin by organosolv process from different varieties of rice husk: Understanding their physical and chemical properties - Singh, Sandip K.; Dhepe, Paresh Laxmikant (Bioresource Technology, 2016)

Solid acid catalyzed synthesis of furans from carbohydrates - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (Catalysis Reviews-Science and Engineering, 2016)
The alternative feedstock, biomass (particularly lignocelluloses), having the profuse availability, is promising for the synthesis of several value-added chemicals which are currently obtained from fossil feedstock. In this article, the synthesis of two extremely significant furan chemicals viz. furfural and 5-hydroxymethylfurfural (HMF) are discussed. In the synthesis of furans from biomass, numerous challenges, i.e., use of edible sugars as substrates, selectivity to furans, their isolation in pure form, reuse of catalyst, environmental issues, etc., are perceived and in the recent past researchers tried to resolve those by developing advance methodologies. This article comprehensively summarizes the latest progress made in the above-mentioned areas and also provides commentary on the analyses of results, rationale for observed activity and mechanisms, etc. It also discusses future aspects of this work.
Keywords: Biomass conversion; carbohydrates; cellulose; furans; furfural; hemicelluloses; HMF; solid acid catalyst

Efficient hydrogenation of concentrated aqueous furfural solutions in to furfuryl alcohol under ambient conditions in presence of PtCo bimetallic catalysts - Dohade, Manisha; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
Furfural (FAL), a major biomass-derived chemical, can be hydrogenated to yield the industrially importantplatform chemical, furfuryl alcohol (FOL). Although heterogeneous catalyst-based methods are known toyield FOL from dilute solutions of FAL, they mainly operate at high temperatures and/or high pressures ofhydrogen and in the presence of organic solvents. In this work, we employ bimetallic PtCo/C catalysts withvarying metal concentrations to achieve the maximum possible FOL yield (100%) at 35 °C under 0.1 MPa H2in water. With concentrated FAL (40 wt%) at 50 °C and under 1 MPa H2pressure, 86% yield of FOL wasobserved. Moreover, eﬃcient catalyst recycling was observed over at least four runs with marginal loss inactivity due to handling error and isolation of FOL in pure form conﬁrmed by NMR and HPLC.Characterization of catalysts with several physico-chemical techniques (XRD, TEM, XPS, ICP, TPR) revealsthe presence of electron-rich Pt and ionic Co species in proximity with each other and these worksynergistically to facilitate maximum possible yield of FOL under ambient conditions and in water medium

From lignocellulosic biomass to furfural: insight into the active species of a silica-supported tungsten oxide catalyst - Bhaumik, Prasenjit; Dhepe, Paresh Laxmikant (ChemCatChem, 2017)
A sol–gel-synthesized silica-supported tungsten oxide catalyst that has Lewis acidity was characterized and employed as a solid acid catalyst in the synthesis of furfural directly from lignocellulosic biomass (isolated xylans and crop wastes). In a one-pot method, 71 % furfural formation from isolated xylan was possible using a water/toluene (1:2 v/v) biphasic solvent system at 170 °C after 10 h over 10 wt % WO3/SiO2. The WO3/SiO2 catalyst in the selective conversion of pentosan from crop wastes (bagasse, wheat straw, and rice husk) yielded 72–87 % furfural under the optimum reaction conditions. Additionally, the catalyst presented excellent recyclability in at least eight runs after simple water washing. From the catalyst characterization studies, it was suggested that silicotungstic-type acid species are anchored on the WO3/SiO2 catalyst that help to achieve a good catalytic activity.

Solid base catalyzed depolymerization of lignin into low molecular weight products - Chaudhary, Richa; Dhepe, Paresh Laxmikant (Green Chemistry, 2017)
For the biorefinery concept to become commercially viable, it is essential to add value to lignin which is the only naturally available aromatic polymer. A one-pot depolymerization of lignin into reactive substituted phenolic compounds (platform chemicals and octane enhancers) with low molecular weight is of paramount importance and for that, the development of an environmentally benign method is necessary. Herein we report the depolymerization of high molecular weight lignin (60 000 Da) over various recyclable solid base catalysts at 250 degrees C over 1 h. Under these conditions, most of the zeolitic catalysts (NaX, NaY, NaP) showed very high yields of low molecular weight products compared to other catalysts (MgO, CaO, HT, HAP). But in particular, over NaX the maximum yield (51%) of low molecular weight products was achieved. Identification and quantification of products was done by GC, GC-MS, HPLC, LC-MS, CHNS, NMR and FT-IR techniques. The revelation of retention of most of the functional groups on products present in lignin was confirmed by FT-IR studies. It is observed that the efficiencies of catalysts were dependent on pH, the cation, the type and concentration of basic sites, etc. A unique study on the product adsorption capacities on solids was done and it is recognized that as the strength of basic sites increases, adsorption enhances.

Understanding interactions between lignin and ionic liquids with experimental and theoretical studies during catalytic depolymerisation - Singh, Sandip Kumar; Banerjee, Subhrashis; Vanka, Kumar; Dhepe, Paresh Laxmikant (Catalysis Today, 2018)
Compared to H2SO4, Bronsted acidic ionic liquid (BAIL, [C3SO3HMIM][HSO4]) catalyzed depolymerization of lignin yielded higher concentration of low molecular weight products under mild conditions (120 degrees C) as proven by GC and GC-MS. To comprehend this disparity in catalytic activity among H2SO4 and BAIL (at similar H+ concentration), experimental techniques [1D(H-1) NMR, 2D(N-15/H-1 HMBC) NMR and RAMAN] have been employed. Based on these studies, it has been proven that the transfer of electron density from substrate to the electron deficient imidazolium ring via formation of hydrogen bond between -OH/OCH3 (substrate) and -N1C2H2N3-(cation) is possible, while the anion plays an important role. Further, density functional theory (DFT) calculations also corroborated this fact by showing a change in the bond angle and decrease in bond length (C-2-H-2 in imidazole), due to the presence of weak and strong hydrogen bonding between the substrate and IL.

Mechanistic investigations on the catalytic transfer hydrogenation of lignin-derived monomers over Ru catalysts: theoretical and kinetic studies - Khan, Tufeil Sartaj; Singh, Dheerendra; Samal, Pragnya Paramita; Krishnamurty, Sailaja; Dhepe, Paresh Laxmikant (ACS Sustainable Chemistry & Engineering, 2021)
The hydrodeoxygenation (HDO) reaction of oxygenated compounds such as lignin-derived phenolics is well studied using molecular H-2 as a hydrogen source, yet the use of high pressures discourages its use on an industrial scale. As an alternative, the catalytic transfer hydrogenation (CTH) pathway provides in situ hydrogenation species, which reduces the need for the high-pressure infrastructure required when molecular hydrogen is used. Nevertheless, this strategy is scantly studied, and in lieu with this, herein we report the kinetic and mechanistic investigations of the CTH strategy for the HDO of guaiacol, phenol, anisole veratrole, and eugenol to their respective products. For potential commercialization purposes, low loading of metal, milder reaction conditions, and high selectivity toward desired products with a high H/C ratio were considered while designing catalysts (0.5 wt % Ru on SiO2-Al2O3, SiO2, Al2O3-acidic, Al2O3-basic, and Al2O3-neutral) for these reactions. As high as 74% cyclohexanol yield from guaiacol was achieved at 225 degrees C in the presence of isopropyl alcohol (IPA) as the hydrogen source and over the Ru/Al2O3-acidic catalyst reduced at 150 degrees C. A detailed kinetic study is carried out to understand the interaction of the substrate and intermediates with the catalyst and the influence of reaction parameters on the product formation. It was observed that the cisisomer of 2-methoxycyclohexanol rapidly undergoes further conversion than the trans-isomer. The experimental observations are substantiated through density functional theory (DFT) studies on Ru(0001) and guaiacol molecule complexes. DFT studies indicate that the adsorption of the cis-isomer is more exothermic as compared to that of the trans counterpart, and the underlying electronic factors are elucidated using charge density difference and density of states plots.
Keywords: catalytic transfer hydrogenation; Cyclohexanol; DFT; Hydrodeoxygenation; kinetics; lignin monomers; Supported metal catalysts

Exploring thermocatalytic pyrolysis to derive sustainable chemical intermediates from plastic waste; role of temperature, catalyst, and reactor conditions - Venkataraghavan, R.; Bhure, Arvind; Khan, Tufeil Sartaj; Shikare, Dipak; Devi, R. Nandini; Dhepe, Paresh Laxmikant (Journal of the Indian Institute of Science, 2024)
Plastic waste is a growing concern globally on account of the increasing use of plastic worldwide, compounded by single-use applications, poor waste collection and management practices, and its consequent leakage into the environment. In addition, plastics are derived from non-renewable fossil resources, and their growing demand is also partly responsible for greenhouse gas emissions and climate change. The aim of this paper is to explore the potential of plastic waste as a material resource, and thermocatalytic pyrolysis as a recycling process, to produce aliphatic and aromatic hydrocarbons, which are important chemical intermediates for various industries. We show that plastic pyrolysis can achieve a high yield of liquid hydrocarbons (similar to 80%) with a suitable distribution of aliphatic and aromatic compounds, by using different pyrolysis conditions and a catalyst. Specifically, this paper demonstrates the possibility of deriving two key classes of hydrocarbons, i.e., aliphatic (C10-C20 hydrocarbons) and aromatic hydrocarbons (xylene, toluene and benzene derivatives) with a yield of similar to 80% liquid hydrocarbons via catalytic pyrolysis. We also briefly discuss the challenges and opportunities, and the environmental and economic implications.